Solving a multi-order fractional differential equation using homotopy analysis method - Jafari H.; Das S.; Tajadodi H. (My University, 2025)
In this paper we have used the homotopy analysis method (HAM) to obtain solution of multi-order fractional differential equation. The fractional derivative is described in the Caputo sense. Some illustrative examples have been presented. © 2010.